Pengaruh Media Audio Visual Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Sosial dalam Implementasi Kurikulum Merdeka di Kelas VII MTs Negeri 01 Rejang Lebong - Teguh Prastiyo; Desy Eka Citra; Saepudin Saepudin (JPT : Jurnal Pendidikan Tematik, 2024)
This study aims to determine the effect of audio visual media on student learning outcomes in social science subjects in the implementation of the Merdeka curriculum in class VII MTs Negeri 01 Rejang Lebong. The type of research used is qualitative research with an experimental approach, this study looks for the relationship between the use of audio visual media and the learning outcomes of students who learn using audio visual media to determine the effect of audio visual media on student learning outcomes. The population of this study consisted of all VII grade students of MTs Negeri 01 Rejang Lebong which amounted to 40 students. The sample of this study amounted to 40 people using Purposive Sampling technique. The data collection techniques used were observation and tests. The data analysis technique used the sample Normality Test (Shapiro-Wilk), Homogeneity Test (Fischer), and used the t test Hypothesis test. Based on the results of statistical calculations showing the tcount value which is greater than the ttable (7.84> 2.100) it can be concluded that there is a significant effect of the use of audio-visual learning media on student learning outcomes in Social Science subjects in class VII MTs Negeri 01 Rejang Lebong. In other words, the use of this learning media positively affects students' academic achievement.